2000
DOI: 10.1139/z00-126
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of largemouth bass and northern pike in allopatric and sympatric assemblages in northern boreal lakes

Abstract: Largemouth bass (Micropterus salmoides) and northern pike (Esox lucius) are top predators in the food chain in most aquatic environments that they occupy; however, limited information exists on species interactions in the northern reaches of largemouth bass distribution. We investigated the seasonal food habits of allopatric and sympatric assemblages of largemouth bass and northern pike in six interior lakes within Voyageurs National Park, Minnesota. Percentages of empty stomachs were variable for largemouth b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 13 publications
4
31
1
Order By: Relevance
“…A change in trophic niche between these conditions is an indication of competition (HEARN, 1987). In six lakes of Minnesota the diets of pike and largemouth bass in sympatric assemblages are indicating the potential for competition, especially during periods of low prey availability (SOUPIR et al, 2000); in this study, however, the food consumed by pike did not differ between sympatric and allopatric assemblages, contrarily of what happens for largemouth bass. It would indicate that M. salmoides are at a significant disadvantage when coexisting with E. lucius.…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…A change in trophic niche between these conditions is an indication of competition (HEARN, 1987). In six lakes of Minnesota the diets of pike and largemouth bass in sympatric assemblages are indicating the potential for competition, especially during periods of low prey availability (SOUPIR et al, 2000); in this study, however, the food consumed by pike did not differ between sympatric and allopatric assemblages, contrarily of what happens for largemouth bass. It would indicate that M. salmoides are at a significant disadvantage when coexisting with E. lucius.…”
Section: Resultscontrasting
confidence: 48%
“…In contrast to M. salmoides, the predator behaviour of E. lucius takes advantage of aquatic vegetation (GRIMM, 1991); in Lake Trasimeno the high percentage of P. antennarius in the pike diet during the winter can be attributed to the reduced availability of forage fish. In a study on the trophic ecology of E. lucius and M. salmoides in six lakes located in Minnesota (U.S.A.) SOUPIR et al (2000) have found that pike was more selective in summer, when the highest proportion of its diet was composed of fish; the uppermost proportions of other food items, mainly insects, were ingested when prey fish densities were lowest. This pattern was similar in both allopatric and sympatric assemblages and was likely due to a fish diet preference in pike.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, just as in this study, others [32]; [33] have shown that pike are flexible with respect to their choice of food -large invertebrate rations and a large diversity of fish species has been noted in pike population. In other studies, however, it has been found that there is a relatively small spectrum of food, and a substantial significance of invertivores in the food [34], [35]. During the study, a relatively large amount of empty stomachs, average 35 %, was noted both in channelized and natural rivers.…”
Section: ____________________________________________________________mentioning
confidence: 62%
“…During the study, a relatively large amount of empty stomachs, average 35 %, was noted both in channelized and natural rivers. The proportion of empty stomachs in recent studies vary between 28 % and 78 % on average, annually (28 % [36]; 50 % [34]; 50 % [32]; 33 % [35]; 54 % [33]; 78 % [37]; 58 % [18]). …”
Section: ____________________________________________________________mentioning
confidence: 99%
“…According to Polat, Yılmaz, and Yazıcıoğlu (2012), pike represents the most important target species for commercial fisheries in Lake Ladik, because pike is one of the main livelihoods of local fishermen. Since the pike is considered as a top predator in the food web in most freshwater ecosystems that it occupies (Soupir, Brown, & Kallemeyn, 2000), it plays an important role as regulator in abundance of prey fishes in most of the aquatic environments (Alp et al 2008). In addition, pike is used for (improving water quality) biomanipulation (Craig, 2008).…”
Section: Introductionmentioning
confidence: 99%